Mari belajar Arab application using game-based learning / Muhammad Azizi Shahril - Shahril, Muhammad Azizi (2017)
The purpose of this project invention was to design and develop Mari Belajar Arab Application which is an enjoyable mobile game application at doing Arabic knowledge drills in Arabic subject for primary school students. The ADDIE method was implemented to design and develop the Mari Belajar Arab Application which is comprises of five phases that need to be completed by sequence which are analysis phase, design phase, development phase, implementation phase and evaluation phase. The findings suggest the combination of the gaming element with Game-Based Learning element can give enjoyment to student in learning Arabic language.